Exploring the Food and Drug Administration's review and approval of Entresto (sacubitril/valsartan). Issue 3 (4th June 2021) - Eadie, Ashley L.; Brunt, Keith R.; Herder, Matthew
Abstract: Federal regulatory agencies such as the United States Food and Drug Administration review pharmacological evidence to ensure the safety and efficacy of new and repurposed pharmaceuticals prior to market approval. The discussions, disagreements and procedural decisions contained within such reviews offer unique insight into a pharmaceutical's strengths, weaknesses and opportunities, yet are often overlooked as a significant source of pharmacological information for research and development. To highlight the value of such resources, we present a case study on Entresto, a first‐in‐class angiotensin receptor‐neprilysin inhibitor for the treatment of heart failure with reduced ejection fraction, and explore the regulatory rationale underlying its market approval. Using information extracted from Entresto's online approval package at Drugs@FDA, we explore some of the procedural complexities underlying market approval of new pharmaceuticals, discuss the broad pharmacological implications contained within regulatory agency grey literature, and highlight opportunities for future therapeutic development. Abstract : Federal regulatory agencies such as the United States Food and Drug Administration review pharmacological evidence to ensure the safety and efficacy of new and repurposed pharmaceuticals prior to market approval. The discussions, disagreements and procedural decisions contained within such reviews offer unique insight into a pharmaceutical's strengths, weaknesses and opportunities, yet are often overlooked as a significant source of pharmacological information for research and development.